L’échec implantaire : revue de la littérature - WEHBÉ, Hiam; BOU-ABBOUD NAAMAN, Nada (International Arab Journal of Dentistry (IAJD), 2011)
Since the 1960s, the introduction of osseointegration principles and improved surgical protocols has resulted in an increasing use of oral implants in clinical practice. Despite their high long-term success rates in the rehabilitation of fully or partially edentulous patients, dental implants failures might occur. The implant failure can be classified as early failure (the osseointegration is not yet established) and late failure (involving a breakdown of the established osseointegration). The aim of this article was to present a literature review regarding mechanism, etiologies and risk factors associated with implant failures.